Recurrent Hydatosis at the Site of Non-union Humerus Fracture - Nourbakhsh, Mohsen (Medknow Publications & Media Pvt Ltd, 2012)
Hydatid disease is still endemic in several regions of the world and is caused by two species of tapeworms, Echinococcus granulosus and Echinococcus alveolaris. It primary involves liver and lung, and bone involvement is relatively rare (0.2–4%), where it is most commonly seen in the spine. The skeletal involvement is usually due to secondary extension such as hematogenous spread. The disease has usually a silent manifestation until a complication exists; so, many cases are diagnosed intraoperatively. Treatment of hydatid disease because of its bone involvement and spillage of fluid with subsequent contamination seeding is difficult, so it has a high mortality rate and many cases will recur. Therefore, we can prevent these occurrences if we treat hydatid disease completely and in the primary stage. Adjuvant medical treatment, if the diagnosis is known, prevents systemic spread and recurrence. Here, we present a primary recurrent hydatosis at the site of non-union humerus fracture. We have pointed out osseous hydatosis as one of the important differential diagnoses in destructive bone lesions and the necessity of its radical resection.